The Stock Market Reaction to Securities Class Action Filings - Damak, Salma; Guermazi, Hend; Beldi, Adel (International Journal of Economics and Financial Issues, 2022)
The purpose of this paper is to investigate stock price reaction to securities class action filings. A standard event study methodology, employing the market model, is applied to determine the abnormal returns both on and surrounding the lawsuit filing day. We utilize the Stanford Securities Class Action Clearinghouse Database (SCAC)[1] to collect the initial sample, which contains data on all securities class action. Insofar as we have eliminated any event that could contaminate the event to capture only the effects linked to the announcement, our sample is then restricted to three events corresponding to three different companies.The results show the absence of a significant reaction for the ten days preceding the lawsuit filings as well as for the ten days following the lawsuit filings. This paper uses stock market reaction to gauge the merit of Securities class action (SCAs) and the results shows that the market has a modest ability to discern meritorious filings from frivolous filings.